Synthesis, Characterization, Anticancer, and Molecular Docking Investigations of Benzothiazole Metal Complexes - Periyasamy, Kavitha; Nainamalai, Vijayakumari (Science and Technology Indonesia, 2025)
The synthesized 2-aminobenzothiazoles based ligand reacted with various transition metal salts were smoothly converted to square planner complexes. The synthesized transition metal complexes are analyzed by using various characterization techniques. Anticancer activity of Schiff base ligand and synthesized metal complexes are examined against human prostate cancer cell line (DU145) MTTassay at different concentration (1, 2, 4, 8, 16, 32, 64, 128, 256, and 512 ug/mL). The IC50 values of metal complexes and free ligand were 16.21 (SBI-Co), 75.98 (SBI-Ni), 25.53 (SBI-Cu), 81.71 (SBI-Zn), and 29.6 (free ligand) ug/mL respectively. Cohasmorepotent against human prostate cancer cell line (DU145). In contrast, the molecular docking study shows, Cu (II) complex has significant inhibition against human 2W3L protein.